2013
DOI: 10.1371/journal.pone.0054193
|View full text |Cite|
|
Sign up to set email alerts
|

Generation and Characterisation of Cisplatin-Resistant Non-Small Cell Lung Cancer Cell Lines Displaying a Stem-Like Signature

Abstract: IntroductionInherent and acquired cisplatin resistance reduces the effectiveness of this agent in the management of non-small cell lung cancer (NSCLC). Understanding the molecular mechanisms underlying this process may result in the development of novel agents to enhance the sensitivity of cisplatin.MethodsAn isogenic model of cisplatin resistance was generated in a panel of NSCLC cell lines (A549, SKMES-1, MOR, H460). Over a period of twelve months, cisplatin resistant (CisR) cell lines were derived from orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(196 citation statements)
references
References 39 publications
9
185
1
1
Order By: Relevance
“…Loss-of-function mutations of cell polarity and cell fate determinants induce neuroblasts to divide symmetrically, leading to an increase in number, tissue overgrowth and ultimately transplantable tumors that resemble mammalian cancers (9). Recent evidence has revealed that cisplatin-resistant subpopulations of NSCLC cells have a putative stem-like character, including increased invasive ability and tumorigenic ability (25). Thus, our findings are consistent with previous studies, which showed an increased proportion of symmetric division in cisplatin-resistant NSCLC cells compared to the parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations of cell polarity and cell fate determinants induce neuroblasts to divide symmetrically, leading to an increase in number, tissue overgrowth and ultimately transplantable tumors that resemble mammalian cancers (9). Recent evidence has revealed that cisplatin-resistant subpopulations of NSCLC cells have a putative stem-like character, including increased invasive ability and tumorigenic ability (25). Thus, our findings are consistent with previous studies, which showed an increased proportion of symmetric division in cisplatin-resistant NSCLC cells compared to the parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoural heterogeneity of cisplatininduced DNA adducts may identify subpopulations of ovarian cancer cells with a putative stem-like signature as shown in non-small cell lung cancer cell lines. 37 Inherent limitations of this phase I study include the small sample size with lack of quality-of-life data and a lack of cost effectiveness analysis, which will play an important role in the future development of this multimodality treatment. The median operative time of almost 8 h reflects the complexity of this combined procedure.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Zhe Zhu 1,2& , Cun-Ping Wang 2& , Yin-Feng Zhang 3 , Lin Nie 1 * rate of initial responses, cisplatin resistance limits its utilizations in cancer patients because some cancer cells develop acquired cisplatin resistance eventually (Negoro et al, 2007;Galluzzi et al, 2012;Barr et al, 2013). The mechanisms of cisplatin resistance are not fully understood yet.…”
Section: Microrna-100 Resensitizes Resistant Chondrosarcoma Cells To mentioning
confidence: 99%